ANALISIS STRUKTUR KELEMBAGAAN PENYELENGGARA E-GOVERMENT PADA PEMERINTAH KABUPATEN SRAGEN TAHUN 2013 - Sekar Kencono, Dewi (Politika: Jurnal Ilmu Politik, 2015)
The e-government enforcement at Sragen Regency has been more than a decade start from 2002. The Council of Empowerment Information Communication Technology (ICT) and Electronic Data Management Office (EDMO). CIO is the supreme institution and hierarchy in charge of the empowerment e-government. Then together with CIO, there is The Council of Empowerment (ICT) as partner labor to give recommendation and suggestion in e-government executive. While EDMO is SKPD that appointed in ICT sector in Government Regency Sragen. Due e-government works necessities in implementing government activities in scopeÂ  Regency Sragen. In this case, indicate there still exists duplication in implementation function and main tasks between CIO, The Council of Empowerment (ICT) Â and EDMO. This duplication dating from â€œPerda SOTKâ€ existence, â€œPerbub Pendayagunaan TIKâ€, â€œPerbub Penjabaran Tugas and Fungsi KPDEâ€, â€œSK CIO formationâ€ and Dewan Pendayagunaan TIK. CIO member adhere in SKPD position, some in between are structural official in EDMO. The embedding of CIO position in structural official SKPD have a purpose to facilitate internal co-ordination e-government enforcement. Such circumstances make EDMO executive core from entire series e-government enforcement. Just as mandated by the regulation of Perbub No.11 year 2008 about Information and Communication Technology both from the disposition, management, presentation, coordination of data, as well as the provision of infrastructure. The Council of Empowerment (ICT) is CIO partner labor. This council has never done either activity or meeting basic budgeting. This kind of e-government enforcement is part of of its EDMO budget. But in the budgetary is not encountered from funding for education or information technology (IT). Â Community as user certainly need to get TIK socialization use that executed by Sragen Regency.Keyword: e-government, institutional,CIO